PENGARUH TRANSPARANSI, TEKANAN EKSTERNAL DAN KOMITMEN MANAJAMEN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Safitri, Friska Dian; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to analyze and to test the effect of transparency, external pressure and managementcommitment to the timeliness of financial reporting. The independent variables are transparency, externalpressure and management commitment whereas the dependent variable is the timeliness of financial reporting.The population is the Financial Management Officer - Local Apparaturs Working Unit (PPK-SKPD) and LocalFinancial Management Officer (PPKD) in the Surabaya city. In this research, based on the criteria which hasbeen done by using purposive sampling, 154 employees have been selected as samples. The data collectiontechniques has been done by issuing questionnaires. The data is the primary data which has been collected byissuing questionnaires to the respondents. The research method is quantitative whereas the analysis techniquehas been done by using multiple linear regression analysis. The results of the research indicates thattransparency, external pressure and management commitment give positive influence and significant impact tothe timeliness of financial reporting.Keywords: transparency, external pressure, management commitment, timeliness of financial reporting.